A Comprehensive Analysis of Research Motivation in Second Language Learning in The Past Ten Years: 近十年国内外二语学习动机研究的综合分析 - Wenjing, Chen (Published by Confucius Institute UNS, 2000)
In the past ten years, academic research on second language motivation has been very fruitful, and the number of published studies in this field far exceeds the characteristics of other language learners. It is worth noting that compared with the prosperity of second language motivation research in foreign journals, the number of domestic literature published in the field of Chinese as a second language acquisition has been significantly reduced. This study selects foreign second language acquisition academic circles and domestic Chinese from January 2010 to August 2021 as the main journals of second language acquisition research, artificially screens research articles with the theme of